PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL MELALUI UPAYA ARBITRASE - Suci Indah Lestari; Tri Reni Novita (Sekolah Tinggi Pariwisata Mataram, 2022)
The COVID-19 pandemic has had a huge impact all over the world. Almost all government and private sectors have been affected by the outbreak. One of the impacts is that the settlement process between the company's dispute relationship and the workers becomes uncontrollable which causes the economy to worsen. As for the entrepreneur who makes a denial of the worker that has been stipulated by the legislation, it will result in a dispute between the entrepreneur and his/her workers. Legal efforts to obtain their rights so that workers get justice by means of workers resolving disputes through arbitration efforts so that both parties get the same justice. This type of research is normative research using primary and secondary materials. The technique of collecting data is based on literature study and document study. The results of the analysis carried out indicate that the settlement of industrial relations disputes through arbitration efforts, namely by the provisions of Law No. 2 of 2004 concerning industrial relations disputes must be based on the agreement of the disputing parties in written form in an arbitration agreement, the contents of which must contain the submission of the agreement. settlement of industrial relations disputes through arbitration.